Two-Year Experience With Latanoprostene Bunod in Clinical Practice. Issue 9 (24th September 2021) - Radell, Jake E.; Sharma, Himanshu K.; Auyeung, Kelsey L.; Paul, Megan E.; Gagliuso, Donna J.; Chadha, Nisha; Tsai, James C.; Serle, Janet B.
Abstract : Precis: We retrospectively reviewed records of patients prescribed latanoprostene bunod 0.024% (LBN) to assess its efficacy and safety in a real-world clinical setting. LBN was efficacious in lowering intraocular pressure (IOP) and had a favorable safety profile. Purpose: The aim of this study was to evaluate the usage of LBN, the first topical nitric oxide-donating prostaglandin analog (PGA) for reducing IOP, in clinical practice. Patients and Methods: Retrospective review identified patients prescribed LBN by 5 glaucoma specialists at an academic center from January 2018 to November 2019. Fifty-six patients (102 eyes) met inclusion criteria of an IOP measured at the visit LBN was prescribed and at 2 visits ≥7 days after beginning treatment, with no surgeries, lasers or medication changes during follow-up. Main outcome measures were IOP, number of ocular medications, and adverse effects. Results: IOP (mean±SD, mm Hg) at the visit LBN was prescribed was 16.2±4.3 on 3.2±1.5 glaucoma medications. IOP at most recent visit was 13.7±3.8 on 3.2±1.6 medications. Mean IOP reduction was 2.1±3.5 ( P <0.0001) at first follow-up, after 38.7±36.5 days, and 2.5±3.3 ( P <0.0001) at last follow-up, after 235.9±160.8 days. Pressure decreased ≥2 mm Hg in 60%, ≥3 mm Hg in 46%, and ≥4 mm Hg in 34% of eyes. All patients received LBN as replacement for a PGA or latanoprost/netarsudil fixed-dose combination. Forty-three patients remained on LBN throughout the follow-up period. Seven were discontinued for insufficient pressure control, 4 for adverse effects including pain and itching, and 2 for financial reasons. Conclusions: In 2 years of clinical use of LBN, patients exhibited IOP reductions that were statistically significant overall and clinically meaningful in 60% of patients. LBN was well-tolerated and may be more efficacious than traditional PGAs.